Structural modeling of Relationship between Organizational Citizenship Behavior and Employee’s Organizational Commitment - Rahmatollah Gholipour Souteh; Hossein Samadi Miarkalai; Hamza Samadi Miarkalai (پژوهش‌های روانشناختی در مدیریت)
Nowadays, for progression and effectiveness, organizations need effective and committed employees that go beyond their duties and achieve growth and maturity. Organizational citizenship behaviors (OCB), which are job behaviors that exist outside of the technical core of the job and some factor such as organizational commitment, have a key role in its improvement. The purpose of present paper is the investigation of relationship between organizational commitment and employee’s organizational citizenship behavior in Red Crescent Society’s Textile Industries of Islamic Republic of Iran. Statistical population of present study includes 180 employees of Red Crescent Society’s Textile Industries of Islamic Republic of Iran and its equal sample includes 106 employees. Data is collected by using standard questionnaires and analyzed by SPSS and LISREL. Results show that the relationship between employee’s organizational citizenship behavior and organizational commitment is positive and significant. This positive and significant relationship is found between organizational citizenship behavior dimensions (except of Affirmative Commitment), and organizational commitment dimensions. In the studied model, the value of indexes of fit (GFI = 0.93, NFI = 0.90 and RMSEA =0.079) demonstrated the suitability of the model.